Immediate effect of dynamic oscillatory stretching vs. neurodynamic sliding technique on stretch tolerance, popliteal angle range and hamstring flexibility in apparently healthy individuals with hamstring tightness: a pre-post clinical trail - R., Ganesh B.; Marwah, Veedika V.; Joshi, Vidhi S. (International Journal of Research in Medical Sciences, 2019)
Background: The hamstrings being postural muscles are prone to tightness which leads to muscular imbalances and inefficiency of daily living activities. Hence, the present study aims to compare two competent techniques Dynamic Oscillatory Stretching (DOS)vs. neurodynamic sliding (NDS) technique. Methods: A Total of 60 subjects were recruited (31 males, 29 females). passive 90-90 knee extension test, modified v sit to reach test and NPRS scale were used to evaluate the range, flexibility and stretch tolerance in participants pre intervention and were allotted into Group A (DOS) and Groups B. The subjects were then re-assessed immediately post intervention. Results: The results were obtained using the independent and dependent t-tests. Post intervention results were suggestive of a significant within group result with a p=0.0001 under all the parameters. Subjects in Group a showed a greater increase in the ROM while, Group B showed a better result in flexibility and stretch tolerance. Conclusions: Both the techniques are efficient and can be incorporated in sports rehabilitation to prevent on site injury thereby improving athlete’s performance.